The Influence of Investment Decisions on Firm Value with Managerial Ownership as Mediation Effect - I Kadek Bagiana; Ida Ayu Nirma Prameswari (Jurnal Ecogen, 2023)
The study discusses the relationship between investment decisions, managerial ownership, and firm value in the manufacturing sector. This study points out that the manufacturing sector is a diverse and large-scale sector, yet the average stock price has declined in recent years. This phenomenon is interesting because there are many factors that can affect firm value, including investment decisions and managerial ownership, and previous research has produced inconsistent findings. To address this issue, the author conducted a quantitative research study using path analysis techniques and SmartPLS software version 4.0.8.8 and employed purposive sampling to select a sample. The results of the analysis indicate that investment decisions have no effect on firm value, but investment decisions have a positive effect on managerial ownership. Furthermore, managerial ownership has a positive effect on firm value and plays a positive mediating role in the relationship between investment decisions and firm value. The author acknowledges that the study has limitations, as it only focuses on investment decisions, managerial ownership, and firm value in the manufacturing sector. Future research should consider adding other variables or modifying the research model using moderation. Moreover, examining more than one sector is recommended to generalize the findings.